2015
DOI: 10.1371/journal.pone.0145173
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Overexpression of Hsp70 Does Not Protect against Cardiac Dysfunction and Adverse Remodeling in a MURC Transgenic Mouse Model with Chronic Heart Failure and Atrial Fibrillation

Abstract: Previous animal studies had shown that increasing heat shock protein 70 (Hsp70) using a transgenic, gene therapy or pharmacological approach provided cardiac protection in models of acute cardiac stress. Furthermore, clinical studies had reported associations between Hsp70 levels and protection against atrial fibrillation (AF). AF is the most common cardiac arrhythmia presenting in cardiology clinics and is associated with increased rates of heart failure and stroke. Improved therapies for AF and heart failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The intercellular-junctions are group of proteins such as connexin 43 (Cx-43) that electrically couple cardiomyocytes for its coordinated depolarization, and its uncoupling has been associated with heart diseases [12]. Also, Hsps are endogenous proteins that act as intracellular chaperones for other proteins through its essential role in protein corrective function (help protein folding and correct its shape), and preventing the unwanted protein aggregations due to the process of aging and in settings of cardiac stress [13]. The most important and best studied class of all Hsps is the 70 kDa (kilodalton) family [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intercellular-junctions are group of proteins such as connexin 43 (Cx-43) that electrically couple cardiomyocytes for its coordinated depolarization, and its uncoupling has been associated with heart diseases [12]. Also, Hsps are endogenous proteins that act as intracellular chaperones for other proteins through its essential role in protein corrective function (help protein folding and correct its shape), and preventing the unwanted protein aggregations due to the process of aging and in settings of cardiac stress [13]. The most important and best studied class of all Hsps is the 70 kDa (kilodalton) family [13].…”
Section: Introductionmentioning
confidence: 99%
“…Also, Hsps are endogenous proteins that act as intracellular chaperones for other proteins through its essential role in protein corrective function (help protein folding and correct its shape), and preventing the unwanted protein aggregations due to the process of aging and in settings of cardiac stress [13]. The most important and best studied class of all Hsps is the 70 kDa (kilodalton) family [13]. We postulated that the induction of HO-1 could improve electrical activity of the cardiac muscle through up regulation of Cx-43 and Hsp70 in MI.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular Hsp70 induced cardiomyocyte inflammation and decreased contractility via toll-like receptors and nuclear factor-κB in primary cardiomyocytes [40]. Moreover, long-term overexpression of Hsp70 failed to prevent cardiac dysfunction and adverse remodeling following chronic heart failure and atrial fibrillation [41]. In this context, the role of Hsp70 in cardiac I/R injury still remains unclear.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%
“…A study suggested that pressure overload could induce MURC messenger RNA (mRNA) expression in cardiomyocytes . Overexpression of MURC in a transgenic mouse model led to atrial fibrillation and chronic heart failure . Ogata et al reported that MURC was involved in the cardiac concentric hypertrophy under pressure overload …”
Section: Introductionmentioning
confidence: 99%
“…9 Overexpression of MURC in a transgenic mouse model led to atrial fibrillation and chronic heart failure. 10 Ogata et al reported that MURC was involved in the cardiac concentric hypertrophy under pressure overload. 11 No conclusive proof has been obtained of how volume overload caused by aortocaval (AV) shunt affects MURC upon hypertrophy in the myocardium.…”
Section: Introductionmentioning
confidence: 99%